Pengaruh Digital Marketing dan Persepsi Harga Terhadap Keputusan Pembelian Pada Toko Rumah Kayu Bordir & Fashion Tasikmalaya: Survei pada konsumen Rumah Kayu Bordir & Fashion Tasikmalaya - Purnomo, Ari Ade; Yusnita, Rita Tri; Pauzy, Depy Muhamad (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This research aims to determine the influence of product design and price perceptions on purchasing decisions (survey of consumers of Tasikmalaya embroidered wooden houses & fashion). The method used is a quantitative approach to the survey method. With a research sample of 100 consumers who buy products at the Tasikmalaya Embroidery & Fashion Wooden House Shop. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 23.0. The research results show that digital marketing at the Tasikmlaya Wooden Embroidery & Fashion Shop has a good assessment classification, price perception at the Tasikmlaya Embroidery & Fashion Wooden House Store has a good assessment classification, purchasing decisions at the Tasikmlaya Embroidery & Fashion Wooden House Store have a very high assessment classification. Simultaneously digital marketing and price perceptions have a significant influence on purchasing decisions. Partially digital marketing has a significant influence on purchasing decisions, partially price perception has a significant influence on purchasing decisions